Math-terpieces : the art of problem-solving - Tang, Greg. (New York : Scholastic Press, 2003)
A series of rhymes about artists and their works introduces counting and grouping numbers, as well as such artistic styles as cubism, pointillism, and surrealism.
Wilson's Children, October 2010.
School Library Journal, August 2003.
Booklist, July 2003.
Horn Book, April 2004.
Kirkus Review, June 2003.
Library Media Connection, March 2004.
Keywords: Set theory -- Juvenile literature; Counting -- Juvenile literature; Set theory; Counting; Art appreciation; Set theory; Counting; Art appreciation; Set theory; Counting; Art appreciation